Diet overlap between Cod (Gadus morhua) and European Flounder (Platichthys flesus) in the central Baltic Sea - Haase, Kevin (SLU/Dept. Of Aquatic Resources, 2018)
The Baltic Sea is a frontrunner in ecosystem analysis and assessment, which have been used also in multispecies fisheries management advice. In the Baltic Sea, the multispecies assessment and management advice have been focused on the pelagic interactions between cod (Gadus morhua), sprat (Sprattus sprattus) and herring (Clupea harengus), by virtue of their well-known ecology. However, the fish in-teractions occurring in the benthic habitat are largely unknown. This study investi-gates, for the first time, the feeding interactions between the most important de-mersal fish species, cod and flounder (Platichthys flesus), in three areas of the eastern Baltic Sea. In this study I use stomach data from 2015 and 2016, collected in the ICES subdivisions 25 – 28 by the Swedish University of Agricultural Sci-ences, Department of Aquatic Resources. The diet of cod differs between the areas but, overall, shows an ontogenetic shift with a decrease of benthic prey and an in-crease of fish preys with size. In the coastal area the amount of benthic prey is al-ways > 50% irrespective of predator size, while in the offshore areas the amount of fish prey increase > 50% with increasing cod size. Conversely, the diet of flounder is relatively constant between sizes and areas. Cluster analyses revealed similarity between the diet of flounder and small-medium size cod in the offshore areas. A significant diet overlap was found between cod < 30 cm and flounder > 20 cm in the offshore area in SD 25, which is mainly driven by similar benthic prey, espe-cially Saduria entomon, in the diet of both predators. These results point to a food competition between cod and flounder, likely augmented by recent increased abundance of Baltic flounder stocks. This competition could decrease the availa-bility of benthic prey for cod, which, in turn, can lead to low condition factor, a re-duction of cod growth and ultimately accentuate the negative effects of hypoxia on cod. Because of all of these reasons, cod and flounder competition could be an-other factor explaining the current bad status of the Eastern Baltic Cod stock.